Penerapan Metode Blended Learning pada Pembelajaran IPS ditengah Pandemi Covid-19 Jenjang di SMP - Suhantoro (STID Raudlatul Iman Sumenep, 2022)
Social studies learning at the junior secondary education (SMP) level during the pandemic must continue to be carried out with various limitations but must not reduce the quality of teaching and learning activities such as face-to-face activities (KTM). Then the policy taken by the education office and implemented by the teacher through distance education (PJJ). There are many choices of how teachers conduct learning activities through distance learning methods, based on the results of the research that the authors carried out, the implementation of the learning turned out to be experiencing many obstacles in learning outcomes. Weaknesses that occur in learning either through google forms, WAG, zoom and social media methods via android are not optimal, due to common obstacles including; signal problems, limited android capacity, limited application mastery and most importantly not all students have android phones. So the most appropriate blended learning model is a combination of offline and online between those who have Android and cannot be balanced in participating in teaching and learning activities. Pembelajaran IPS ditingkat pendidikan menengah pertama (SMP) di masa pandemic harus tetap dilaksanakan dengan berbagai keterbatasan namun tidak boleh mengurangikualitas kegiatan belajar mengajar seperti kegiatan tatap muka (KTM). Maka kebijakan yang diambil oleh dinas pendidikan dan dilaksanakan oleh guru melaui pendidikan jarak jauh (PJJ). Banyak pilihan bagaiman guru mengadakan kegiatan belajar melalui metode pembelajaran jarak jauh, berdasarkan hasil penelitian yang penulis laksanakan, terhadap pelaksanaan pembelajran tersebut ternyata banyak mengalami kendala dalam hasil pembelajaran. Kelemahan yang terjadi pada pembelajaran baik melalui google form, WAG, zoom dan metode medsos melalui anderoid ternyata tidak maksimal, dikarenakan kendala umum diantaranya; masalah sinyal,kapsitas anderoid yang terbatas, keterbatasan pengusaan aplikasi dan yang paling utama ialah tidak semua siswa memiliki handphone anderoid. Maka pembelajaran model blanded yang paling tepat ialah perpaduan luring dan daring antara yang mempunyai anderoid dan tidan bisa seimbang dalamengikuti kegiatan belajar mengajar